Social Actions of Social Drinkers in Building Business Relationships - Najwa Zahira; Khaerudin Imawan; Welly Wihayati (Syntax Corporation Indonesia, 2024)
The café is an interaction space for Social Drinkers to discuss and collaborate in making decisions and building business relationships, several businesses have been born from the communication carried out by Social Drinkers in Sanes Kape. Examples are Peony which is engaged in fashion and hijab, Nawaicrrative in advertising agencies, and Komunalab in social media handling. The café offers an atmosphere that supports productive social action. This study aims to analyze the social actions of Social Drinkers in Sanes Kape in building business relationships, identify the types of social actions carried out, explain the role of Sanes Kape as a social action space that supports the formation of business relationships, and obtain findings and conclusions that are useful for the development of cafes as social action spaces that are conducive to building business relationships. This study uses a qualitative method with a case study approach supported by Max Weber's theory of social action. The results of the study show that the interaction in this café reflects rational-instrumental, rational-value, and affective social actions in building strong business relationships. The findings show that Sanes Kape is a strategic place for Social Drinkers who want to build profitable business relationships.